PENGARUH RATING OBLIGASI DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL DENGAN DEBT TAXSHIELD SEBAGAI VARIABEL MODERASI DI PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI TAHUN 2011-2015 - Maisyaroh Maisyaroh; Edyanus Herman Halim; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to analyze Debt Tax Shield moderate the influence of bond rating on capital structure. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) period of 2011-2015. Dependent variable in this research is capital structure measured by Debt to Equity Ratio (DER), while independent variable is bond rating and firm size and moderation variable is Debt taxshield. This study has a population of 137 companies in manufacturing companies listed on the Indonesia Stock Exchange period 2011-2015. This research uses purposive sampling technique and sample which fulfill as many as 44 companies. The method of data processing using multiple regression analysis and regression of moderation. SPSS software version 21.00. The result of the research shows that the variable of bond rating has a significant positive effect to the capital structure in the manufacturing company for the period of 2011-2015. The size of the company has a significant positive effect on capital structure in the manufacturing company for the period of 2011- 2015. Debt Tax Shield does not moderate the bond rating relationship to the capital structure and is insignificant as well as with the positive variable value in the manufacturing company for the 2011-2015 period. Debt Tax Shield moderates the firm size relation to the capital structure and is significant and with the negative variable value in the manufacturing company for the period of 2011- 2015.Keywords : Bond rating, Company size, Debt Tax Shield, capital structure